THE PROCEDURE OF IMPLEMENTATION OF ELECTRONIC SCIENTIFIC JOURNAL USING THE OPEN JOURNAL SYSTEMS SOFTWARE PLATFORM - Spirin O.; Luparenko L.; Novytskyi O. (Kherson State University, 2017)
The article deals with the procedure of implementation of the electronic scientific periodical edition using electronic open journal systems (EOJS). It is specified the activities at each of its stages (prognostic, organizational, technical, preparatory, practical, generalizing and prospective). The recommendations on the main aspects of the electronic journal implementation are given: the normative and legal basis for the functioning, their types, scientific scope, target audience, economic model, editorial policies and periodicity of publication; the software selection for the editorial and publishing process support, the Open Journal Systems (OJS) user roles system; the expected type and format of the journal content, the type of it access, including open access, archiving, indexing and information and analytical monitoring of published scientific works; the formation of the editorial board and staff, the involvement of ICT professionals, their duties and workload, the users and technical team training.